2019
DOI: 10.2147/dddt.s192632
|View full text |Cite
|
Sign up to set email alerts
|

<p>Low-dose adefovir dipivoxil&ndash;induced hypophosphatemia osteomalacia in five chronic hepatitis B virus&ndash;infected patients. Is low-dose adefovir dipivoxil&ndash;induced nephrotoxicity completely reversible?</p>

Abstract: Adefovir dipivoxil (ADV) is one of the most important nucleostide analogues currently in use for the treatment of chronic hepatitis B virus (HBV) infection. Low-dose ADV-induced nephrotoxicity in most cases was reported to be reversible after the discontinuation of ADV or by decreasing the dose of ADV. In our study, we have 5 documented cases of low-dose ADV-induced hypophosphatemia osteomalacia with or without Fanconi syndrome which were diagnosed in our hospital between 2010 and 2017. Three patients were obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Factors identified as predictive of kidney damage and Fanconi syndrome [17] include: age over 40 years, rural environment, renal injury, eGFR < 90 ml/min/1.73 m 2 , hypertension, diabetes, cirrhosis, and ADV treatment exceeding 24 months. Many cases of hypophosphatemic osteomalacia induced by low-dose adefovir (10 mg daily) have been reported [6,7], especially in Asian countries [18][19][20].…”
Section: Drug-induced Fanconi Syndromementioning
confidence: 99%
“…Factors identified as predictive of kidney damage and Fanconi syndrome [17] include: age over 40 years, rural environment, renal injury, eGFR < 90 ml/min/1.73 m 2 , hypertension, diabetes, cirrhosis, and ADV treatment exceeding 24 months. Many cases of hypophosphatemic osteomalacia induced by low-dose adefovir (10 mg daily) have been reported [6,7], especially in Asian countries [18][19][20].…”
Section: Drug-induced Fanconi Syndromementioning
confidence: 99%
“…The main characteristics of 32 patients with ADV-induced FS, including eight patients in our institution and 24 published cases, are summarized in Table 4 . 5 , 18 , 22 , 23 , 36 43 …”
Section: Reviewmentioning
confidence: 99%
“… 52 However, some recent studies indicated that renal damage induced by ADV may be irreversible. 18 , 23 , 29 , 34 However, it may be not sufficient to evaluate renal function using only β2-M. 18 Thus, further comprehensive research using longer treatment periods and considering eGFR, β2-M, RBP, and other potential biomarkers is needed to clarify whether renal dysfunction induced by ADV is completely recoverable. Moreover, a study using a 6‐month follow‐up period found that patients with chronic kidney disease and tubule acidosis have a poor prognosis.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations